Aristoi - Williams, Walter Jon 1953- (Doherty, 1993)
Successful in its efforts to create a glittering interstellar empire, founded on the use of an ultra-advanced computer and bioengineering technology, humankind becomes the prey of its own creation, the Aristoi
"A Tor book"--T.p. verso. - Reprint. Originally published: 1992
Keywords: Science fiction